PENGARUH PEMBERIAN AIR KELAPA MUDA (Cocos nucifera) TERHADAP KELELAHAN KERJA PADA NELAYAN DI TAMBAK MULYO SEMARANG - Buwana, Prasena Aji; Widjasena, Baju; Suroto, Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
The background of this study was fatigue can lower labor productivity, as well as causing accidents. Fishermen are jobs at risk of fatigue, so the coconut water is needed to overcome the fatigue. Coconut water containing electrolyte ions needed by the body when dehydration, namely potassium and sodium. The aim of this study was to determine the effect of coconut water to the exhaustion of work on fishing. This research method using quasi experiment with the type of study design One group pretest-posttest design. Fishermen many as eight people were respondents in this study. Respondents his fatigue was measured using a Simple Reaction Timer application. Measurements were taken twice, namely at the moment before the given coconut water, and when after given coconut water. Results showed that Mean fatigue on fishermen also decreased by 155.8 mil / sec. Besides, there are differences between groups before given after given coconut water with coconut water. The significant value of <0.05 (p = 0.000) through the Paired T - Test. The conclusion from this study is the coconut water can reduce the speed of the reaction time of 155.8 milli / sec, which means lower levels of fishermen’s fatigue. Suggestions for this study, the fishermen have to use head’s protection such as hats in case to prevent heatand consuming coconut water to replace body fluids lost through dehydration.